Unveiling Antimicrobial Resistance Trends in Malaysia: A Comparative Study with Global Pattern - Ismail, Andi Regina Acacia; Lisa, Guymer; Diana, Katharina; Vasso, Nicola; Kylie, Anna (International Journal of Clinical Inventions and Medical Sciences (IJCIMS), 2024)
This research explores the patterns of antimicrobial resistance (AMR) in Malaysia, with a focus on major bacterial strains such as MRSA, E. coli, Klebsiella, and Pseudomonas. Data from clinical microbiology laboratories in both public and private hospitals was collected using a cross-sectional, observational study design. Analysis of resistance rates indicated that MRSA showed a resistance rate of 45%, which was notably greater than the global standard of 30% (p < 0.01). Likewise, E. coli, Klebsiella, and Pseudomonas displayed resistance rates of 55%, 40%, and 35%, respectively. These results emphasize the increasing problem of AMR in Malaysia, especially in urban healthcare settings, where resistance rates were higher than in rural areas. In the future, researchers need to enhance AMR monitoring systems and encourage responsible use of antibiotics in Malaysia. Comparison with worldwide databases like WHO GLASS and CDDEP indicates that focused efforts in urban areas are needed to address the increasing resistance rates. This research highlights the need to tackle AMR promptly by collaborating among policymakers, healthcare providers, and public health institutions. Additional research is required to assess the efficiency of existing methods and discover innovative ways to address AMR within the area.